2021
DOI: 10.26501/jibm/2021.1102-006
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of A New Islamic Work Ethics Scale for Healthcare Providers in Emergency Departments (EDIWES)

Abstract: Purpose: Research on work ethics has acquired considerable scholars’ attention. Research on employees’ religion-oriented ethics, particularly Islamic Work Ethics (IWE), has remained relatively narrow in healthcare settings. This study aims to develop and validate a scale to measure Healthcare Providers (HCPs) IWE in Emergency Departments (EDs). Design/methodology/approach: This study was conducted on HCPs who work at EDs in Jordan. The scale goes through a series of validation processes, including content vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The scale of job satisfaction has reported reliabilities above 0.90. IWE was measured using an instrument developed by Al Smadi et al (2021). This instrument consisted of three dimensions and 17 items: obligation of healthcare providers to their patients’ seven items, obligation of supervisors to their subordinates’ five items and obligation of healthcare providers to their colleagues’ five items.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The scale of job satisfaction has reported reliabilities above 0.90. IWE was measured using an instrument developed by Al Smadi et al (2021). This instrument consisted of three dimensions and 17 items: obligation of healthcare providers to their patients’ seven items, obligation of supervisors to their subordinates’ five items and obligation of healthcare providers to their colleagues’ five items.…”
Section: Methodsmentioning
confidence: 99%
“…Khanifar et al (2012) identified eight dimensions of Islamic work value: service-oriented morale, effort and perseverance, work spirituality motivation, continuous improvement, work obligation, justice, Itqan, and work solidity. Finally, Al Smadi et al (2021) identified three dimensions of IWE in the healthcare field: obligation of healthcare providers to their patients, obligation of supervisors to their subordinates, and obligation of healthcare providers to their colleagues. Ali (1988) is credited with being the first to write about IWE scaling and measurement.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The researchers further identified three domains of work ethic that include Protestant Work Ethics (originated from teachings of Christianity), Confucius Work Ethics (originated from Chinese Confucius philosophy) and Islamic Work Ethics (having roots in Islamic teachings) (Asadullah et al, 2020). Organizations benefit from good cooperation because it improves teamwork, job quality, instils harmony and the rights of each member inside the organisation, and improves communication (Al-samdi et al, 2021). Among all the codes of work ethic, the Islamic Work Ethics (IWE) became popular because of its instrumentality for job performance because it treats work as noble task instead of mere calculative act (Asadullah et al, 2020).…”
Section: Introductionmentioning
confidence: 99%